Поэзия - Пастернак Борис Леонидович (Пушкинская библиотека, 2000)
Экземпляры: аб. (2000) / Инвентарный номер: 42461 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: П 19 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6-5